Kompetensi Komunikasi Antarbudaya Siswa Sekolah Menengah Atas - Moulita Moulita (Universitas Medan Area, 2019)
The objective of the research is to find out how the intercultural communication competence possessed by the students of Sultan Iskandar Muda High School Medan. Through qualitative approach by applying case study method, the problem in this research will be answered by using an intercultural communication competence model developed by Chen and Starosta which consists of three components: affective, cognitive, and behavioral. The results of the study shows that the research subjects in general have had intercultural communication competence especially on elements: cultural knowledge, self-concept, open-mindedness, nonjudgmental, social relaxation, interaction management, and social skills.Keywords: intercultural communication competence, students, Sultan Iskandar Muda High School